A non-redoxable electron-cloud-channel oxide electrode: Atmosphere independent metallic perovskite CaVxO3-δ. (15th March 2022) - Choi, Soon-Mok; Meang, Eun-Ji; Tak, Jang-Yeul; Seo, Won-Seon; Lee, Soonil
Abstract: An alternative oxide anode material to surpass Ni electrode in the solid oxide fuel cell (SOFC) technology, used at high temperature range (500–1000 °C), is needed for the SOFC industry. We investigated an advanced perovskite oxide electrode, CaVx O3-δ system, for the alternative oxide anode material. The CaVx O3-δ powder and bulk were fabricated by using an atmosphere controlled solid-state reaction method and spark plasma sintering (SPS), respectively. The bulk specimen showed 3-3 type nonstoichiometric composite structure, and the electrical conductivity and Seebeck coefficient measurements revealed metallic n -type conductivity. Surprisingly, the high electrical conductivity (> 12, 000 S/cm at room temperature; >1000 S/cm at 1000 K) was stable at different atmospheres between air and reduction atmospheres, attributing to a non-redoxable electron-cloud-channel phase protected by a redoxable protection phase. It is believed that the CaVx O3-δ system can be used as a promising and atmosphere stable oxide electrode in the fuel cell technology and other applications. Graphical abstract: Schematic diagram of a non-redoxable electron-cloud-channel (ECC) phase, protected by a redoxable protection phase, in the 3-3 composite formed spontaneously in the reduced CaVx O3-δ . The highly reduced phase can generate more electrons and simultaneously play as a channel for electrons to move easily. Image, graphical abstract